2022
DOI: 10.1007/s00068-022-01892-4
|View full text |Cite
|
Sign up to set email alerts
|

A clinical decision aid to discern patients without and with midfacial and mandibular fractures that require treatment (the REDUCTION-II study): a prospective multicentre cohort study

Abstract: Purpose To assess the diagnostic accuracy of physical examination findings and to construct clinical decision aids to discern emergency department patients without and with midfacial and mandibular fractures that require treatment. Methods A prospective multicentre cohort study was conducted in four hospitals in the Netherlands. Consecutive maxillofacial trauma patients were included whereupon each patient underwent a standardized physical examination cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A recent study focused on how a combination of clinical findings can be used to predict maxillary and mandibular fractures. [9] However, the study of combining TBT with other clinical signs as a clinical decision tool is limited. A previous study concluded that negative TBT may be useful to rule out mandibular fracture, as the combined sensitivity was 95.4%, [6] but TBT should be used in adjunct with other clinical findings, as its sensitivity may be as low as 85.0%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study focused on how a combination of clinical findings can be used to predict maxillary and mandibular fractures. [9] However, the study of combining TBT with other clinical signs as a clinical decision tool is limited. A previous study concluded that negative TBT may be useful to rule out mandibular fracture, as the combined sensitivity was 95.4%, [6] but TBT should be used in adjunct with other clinical findings, as its sensitivity may be as low as 85.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion was defined as an objectively identified traumatic misalignment of the maxillary and mandibular dental arches. [9] Tenderness on palpation and swelling was defined as the presence of pain during palpation and swelling of the maxillary region (maxillary sinus, infraorbital rim, zygomaticomaxillary complex, Le Fort I, II, III complex and maxillary dentoalveolar complex) and mandibular region (symphyseal or parasymphyseal region, body, angle, ramus, coronoid process, condylar process and mandibular dentoalveolar complex). [9] For TBT, the patient was asked to bite on a tongue depressor until it was broken against twisting motion by an examiner, resulting in a negative test.…”
Section: Data Collection and Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The closed reduction procedure involves using intraoral elastic traction on the maxillary and mandibular teeth to gradually reposition them laterally. 16 Tooth occlusion can be achieved by IMF and elastic traction. The treatment plan also includes general health care measures, such as administering antibiotics and analgesics, roborantia, nutritious food, maintaining oral hygiene, and providing physiotherapy.…”
Section: Discussionmentioning
confidence: 99%